Nabis succini n. sp. Eine Nabide aus dem Bernstein Ostpreußens (Hemiptera Heteroptera). - Jordan, Carl Hermann Christian (Contributions to Entomology = Beiträge zur Entomologie, 1952)
Nomenclatural Actssuccini Jordan, 1952 (Nabis), spec. n.